Pediatric snakebite in sub-Saharan Africa: clinical predictors, outcomes, and gaps in care : a systematic review [data] - Mayeden, Samuel; Wirth, Margit; Agbaria, Nisreen; Shaikh, Masood; Dambach, Peter; Wilson, Michael; Horstick, Olaf; Camacho, Salvador; Lang, Hans-Jörg; Deckert, Andreas (Universität, 2026)
This dataset contains study-level aggregated data underlying the systematic review “Pediatric Snakebite in Sub-Saharan Africa: Clinical Predictors, Outcomes, and Gaps in Care.” It includes extracted characteristics of included studies, quality assessment results, search strategies, antivenom use by country, clinical outcomes, prognostic indicators, and summary tables referenced as Supporting Information (S1-S6 Tables) in the manuscript. The data contain no individual patient information and are shared to support transparency, reproducibility, and reuse.
Gesehen am 02.02.2026
Keywords: Forschungsdaten; Datenbank